American modern(ist) epic : novels to refound a nation - Nemmers, Adam (Clemson University Press, 2021)
"American Modern(ist) Epic argues that a cadre of minority novelists revitalized the classic epic form in an effort to recast the United States according to modern, diverse, and pluralistic grounds. These modern(ist) epic novels undermined and revised the foundational ideology of the United States, modernizing the epic form in an effort to refound the nation"--